Islam - ISNA Convention Reporters Committee (International Institute of Islamic Thought, 2004)
ISNA’s Forty-first Annual Convention, held in Chicago (September 4-6, 2004), offered about 100 sessions and was cohosted by the Council of Islamic Organizations of Greater Chicago (CIOGC). Over 400 Chicago Muslim volunteer organizations offered their support, resources, and talents under CIOGC’s leadership. The Friday night Interfaith Unity Banquet was dedicated to interfaith dialogue. The invitation-only event seeks to energize attendees, including politicians running for office in the Chicago area, to continue their efforts and to recognize those who are trying to build bridges between different faith communities. The Rev. Stanley L. Davis, Jr., was given a plaque for his continuing work in interfaith relations plus his dedication to peace and justice. The Fifth Annual Community Service Recognition Luncheon, hosted by the ISNA Development Foundation, was addressed by Cherif Bassiouni, a respected attorney and professor at DePaul University, who is also president of the International Human Rights Law Institute. He declared: “It makes me angry when Muslims apologize for Islam. I am proud to be a Muslim.” For the first time, a female Muslim activist, Sharifa Alkhateeb, received the Mahboob Khan Community Service Award, which recognizes outstanding service to the Muslim community in North America. Alkhateeb, recognized for her work in various causes, especially those concerning women, could not attend. Her husband Mejdi accepted the award on her behalf, while her sister read her acceptance speech. Former ISNA president Muzammil Siddiqui also received the award ...